Tingkat Kepuasan Jamaah pada Pelayanan Ibadah Haji di Kemenag Kota Semarang - Lestari, Siti Kris Fitriana Wahyu (Department of Da'wah Management, Faculty of Da'wah, IAINU Tuban, 2024)
This research aims to measure pilgrims' satisfaction with Hajj services at the Ministry of Religion, Semarang City. This research uses quantitative methods with a focus on describing community satisfaction with the Hajj services of the Department of Religion of Semarang City. The research was carried out by taking a population sample, namely Hajj pilgrims, by collecting data using a series of questions arranged in a questionnaire. The sample was 95 pilgrims from the Ministry of Religion of Semarang City from a total population of 2,095 people. This research uses simple regression analysis using SPSS 17.0. The results of this research indicate that there is a significant positive influence between Hajj services on pilgrim satisfaction in the Ministry of Religion, Semarang City. This is shown using the sig value. to calculate the significance test results in the Anova table of 0.000. When compared with α = 0.05, the Sig value. smaller than α (sig. < α), namely 0.000 <0.05, so this research hypothesis is accepted. The resulting interpretation is that the R-square (R2) value is 0.962 or 96.2%. This value shows that variable X (service) to Y (satisfaction) is 96.2% and other variables that influence variable Y (satisfaction) are 3.8%. Keywords : Quality, Service, Hajj